Optimal Designed Formulations of A Lactic Acid Bacteria Consortium for Azo Dyes Decolorization with Sucrose As A Single Carbon Source - Nidtaya Tantiwa (Science Faculty of Chiang Mai University, 2019)
This research studied the decolorization of azo dyes, methyl orange and remazol black b, by the lactic acid bacterial consortium. A process of the decolorization was separated into two stages; firstly, lactic acid bacteria (LAB) was cultivated with sucrose as a sole carbon source and then subsequently added to azo dyes decolorization under a static condition. The pure culture of each LAB strains showed high decolorized efficiency on both methyl orange and remazol black b. Then, the experimental design mixture was used to optimize the optimal proportion of mixed culture of the LAB and found the best proportion of LAB mixed culture that could decolorize azo dyes at the concentration of 100 mg/L. The azoreductase activity of the mixed culture significantly increased up to 45% which was higher than the activity by the individual strains. FTIR spectra confirmed that the lactic acid bacterial consortia had the ability on the azo dye decolorization by removing the azo group from the azo dye molecule, which was showed the absence of -N=N- stretching vibrations on methyl orange and remazol black b structures.